2022
DOI: 10.1155/2022/5662117
|View full text |Cite
|
Sign up to set email alerts
|

Lane-Filtering Behavior of Motorcycle Riders at Signalized Urban Intersections

Abstract: In developing countries, motorcycle riders typically perform lane filtering at signalized urban intersections. This study aims to determine the factors that affect the lateral clearance of motorcycle riders as they travel between two lanes of mixed traffic at signalized urban intersections in developing countries. In this study, an onboard measurement device was developed to measure the lane-filtering behavior of motorcycle riders. It was installed on a test motorcycle to continuously record the lateral cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The higher the number of stopping motorcycles in the exclusive stopping space during the red light, the greater the reduction in the start-up time of the traffic flow [54]. A filtering lane allows motorcycle riders to filter between a queue of stopping vehicles and access the exclusive stopping space for motorcycles more easily [2]. In addition, the findings indicated that motorcycle riders prefer to stop at locations covered by the shadows of trees or buildings.…”
Section: Discussion Toward Recommendation For Implementationmentioning
confidence: 99%
See 4 more Smart Citations
“…The higher the number of stopping motorcycles in the exclusive stopping space during the red light, the greater the reduction in the start-up time of the traffic flow [54]. A filtering lane allows motorcycle riders to filter between a queue of stopping vehicles and access the exclusive stopping space for motorcycles more easily [2]. In addition, the findings indicated that motorcycle riders prefer to stop at locations covered by the shadows of trees or buildings.…”
Section: Discussion Toward Recommendation For Implementationmentioning
confidence: 99%
“…Some of them studied the behavior of motorcycle riders approaching or passing through signalized intersections. A few studies investigated the maneuvering behavior in queues [1,2] and the crossing behavior [29,30] of motorcycle riders at signalized urban intersections. These studies explored various behaviors of motorcycle riders riding along urban road networks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations